Significant effect of oxide on mechanical properties of friction-stir-welded AA2024 joints. (2nd January 2017) - Niu, P.; Li, W.; Zhang, Z.; Wang, F.; Feng, Y.; Fu, M.
Abstract : A 30–40 μm thick oxide layer was prefabricated on the top, butt or bottom surfaces of AA2024 sheets by micro-arc oxidation, which were then friction stir welded. Sheets without oxide layer were also welded with blowing oxygen along the weldline during welding for comparison purposes. Results reveal that the tensile properties depend on the amount and distribution of the residual oxide impurities in the joints. The oxide layer on the butt surface leads to continuously distributed oxide impurities in the shoulder-affected zone near the advancing side, and a 159 MPa maximum degradation in tensile strength was noticed. Moreover, the oxygen blowing during welding has a little influence on the joint tensile strength and no oxide was detected in the joint.